Long-Term Effects of “Yer Malhami” Fertilizer: A Study on its Impact and Effectiveness - Sherkuzieva Guzal; Salomova Feruza (BIO Web of Conferences)
This study evaluated the long-term toxicological and hygienic effects of the biological fertilizer “Yer Malhami” in white rats. The study used hygienic, toxicological, biochemical and statistical methods in accordance with the guidelines for environmental testing of bioinsecticides. A 12-month chronic experiment was conducted focusing on potential gonadotoxic, embryotropic and mutagenic effects. Rats were administered different doses of “Yer Malhami” and changes in body weight, reproductive cycles and cellular composition were observed. The results showed no significant disturbances in reproductive cycles or spermatogenesis, and chromosomal aberration tests showed no mutagenic effects. Although a slight decrease in fetal survival was observed at toxic doses, this was due to general toxicity rather than specific reproductive harm. The study concluded that Yer Malhami is safe for long-term use as a biofertilizer, with no adverse effects on reproductive or genetic health in the animals tested. Further studies are recommended to examine its safety in different species and environmental conditions.